2018
DOI: 10.1007/s10484-018-9391-7
|View full text |Cite
|
Sign up to set email alerts
|

EEG Spectral Analysis on OM Mantra Meditation: A Pilot Study

Abstract: Mantra meditation is easy to practice. "OM" Mantra is the highest sacred symbol in Hinduism. The present study investigated the temporal dynamics of oscillatory changes after OM mantra meditation. Twenty-three naive meditators were asked to perform loud OM chanting for 30 min and the EEG were subsequently recorded with closed eyes before and after it. To obtain new insights into the nature of the EEG after OM chanting, EEG signals were analyzed using spectral domain analysis. Statistical analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 19 publications
2
13
1
4
Order By: Relevance
“…In contrast, Hinterberger et al ( 2016 ) reported that Theta healers (CDM) presented a decreased theta power when compared with baseline, while their clients had no change. This lack of change in beginners is corroborated by Harne and Hiwale ( 2018 ) who reported no spectral changes after one session of “Om” chanting (CDM-FA).…”
Section: Spectral Featuressupporting
confidence: 61%
“…In contrast, Hinterberger et al ( 2016 ) reported that Theta healers (CDM) presented a decreased theta power when compared with baseline, while their clients had no change. This lack of change in beginners is corroborated by Harne and Hiwale ( 2018 ) who reported no spectral changes after one session of “Om” chanting (CDM-FA).…”
Section: Spectral Featuressupporting
confidence: 61%
“…To verify the impact of mindfulness adjustment on the EEG signals of the subjects, we conducted ANOVA using Statistical Package for the Social Sciences (SPSS) software (Wang et al, 2015). ANOVA (Harne and Hiwale, 2018) included the influence of mindfulness adjustment on frequency bands and the influence of different frequency bands in different brain regions. In neurofeedback, the changes in alpha, theta, and gamma waves are usually used as evaluation indicators, and corresponding improvement and treatment are executed by strengthening these waves.…”
Section: Resultsmentioning
confidence: 99%
“…Oscillations in the theta band are thought to reflect top-down influences related to working memory and memory retrieval (Klimesch, 1999;Sauseng et al, 2005;Demiralp et al, 2007;Sauseng et al, 2010), and are linked to the activation of autobiographical memories (Steinvorth et al, 2010) as well as to mental time travel (Lavallee and Persinger, 2010) and, more generally, to the level of mental workload (So et al, 2017). While these aspects of theta oscillations could be related to mind-wandering, multiple reports show enhanced theta power in mindfulness meditators, as well as in meditators following other contemplative traditions (Lagopoulos et al, 2009;Xue et al, 2014;Lomas et al, 2015;Harne and Hiwale, 2018). Furthermore, frontal theta oscillations are inversely correlated with default mode activity, suggesting that these oscillations signal episodes of sustained attention (Scheeringa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%